2018
DOI: 10.1186/s12966-018-0719-8
|View full text |Cite
|
Sign up to set email alerts
|

Changes in diet through adolescence and early adulthood: longitudinal trajectories and association with key life transitions

Abstract: BackgroundEarly adulthood is a period associated with poor diet and rapid weight gain. This is also an age of transition, including environmental, social and lifestyle changes which may be associated with changes in diet. We assess longitudinal associations between four early adulthood life transitions (leaving home, leaving education, entering employment, and cohabitation) and changes in consumption of fruit, vegetables, confectionery and sugar-sweetened beverages (SSBs).MethodsParticipants (n = 1100) from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
138
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(163 citation statements)
references
References 43 publications
8
138
1
6
Order By: Relevance
“…The rapid weight gain during young adulthood coincides with marked declines in physical activity (PA) and dietary habits . Specifically, a longitudinal cohort study among 640 Canadian adolescents demonstrated a 24% decrease in PA (equivalent to 1 MET/day) during a 12‐year transition from adolescence to early adulthood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rapid weight gain during young adulthood coincides with marked declines in physical activity (PA) and dietary habits . Specifically, a longitudinal cohort study among 640 Canadian adolescents demonstrated a 24% decrease in PA (equivalent to 1 MET/day) during a 12‐year transition from adolescence to early adulthood.…”
Section: Introductionmentioning
confidence: 99%
“…This means they have lower intakes of nutrient‐rich foods such as fruits and vegetables, and wholegrains, and higher intakes of energy‐dense, nutrient‐poor foods such as processed meats and sugar‐sweetened beverages . These negative behavioural patterns are attributed to key transitional changes that occur during young adulthood including changes in living situation (ie, moving out of home), social environment and influences (ie, developing stronger peer networks and partner relationships), employment status (ie, starting tertiary education), and financial situation (ie, becoming more financially independent) …”
Section: Introductionmentioning
confidence: 99%
“…38 One study investigated changes in diet on leaving full-time education. 9 This study analysed leaving full-time education at any age rather than specifically leaving university, but the study population year period. 39 Miller et al reported no significant changes in MVPA associated with starting employment.…”
Section: Leaving High School or Starting University: Changes In Bodmentioning
confidence: 99%
“…6 During this period, physical activity decreases, 7 and changes in diet are observed, including decreases in fruit and vegetable consumption in adolescence and increases in diet quality in early adulthood. 8,9 Lifestyle behaviours developed during early adulthood are thought to track into adulthood, influencing later health outcomes. 10 Study of this transitionary period presents an opportunity to understand the impact of changing social and physical environments on lifestyle behaviours, in order to support the development and targeting of public health policy and interventions.…”
mentioning
confidence: 99%
“…The period of life from late adolescence to early adulthood is the time when prevalence of overweight and obesity rises the fastest [2], and an important time for understanding changes in determinants of obesity such as diet and physical activity. It is also a time when individuals go through many life transitions, likely to be associated with changes in the determinants of dietary behaviours [3]. Better understanding of how diet changes across this age range will lay a foundation for further investigation of the determinants of changes in diet and evidence on how and when best to intervene to promote establishment of a high quality diet which persists in adulthood.…”
Section: Introductionmentioning
confidence: 99%